Structural isomerism in the [(Ni@Sn9)In(Ni@Sn9)]5− Zintl ion† - Zhang, C; Morgan, H; Wang, Z; Liu, C; Sun, Z; McGrady, J (Royal Society of Chemistry, 2019)
A new Zintl cluster, [(Ni@Sn9)In(Ni@Sn9)]5−, has been isolated in two distinct isomeric forms, one where both Ni@Sn9 units are coordinated to the bridging In atom in an η3- mode, the other where one is η3- and the other η4-. Density functional theory indicates that the energetic separation between these two structures is minimal, suggesting that crystal packing plays a decisive role in the structural chemistry. A comparison of the electronic structure of [(Ni@Sn9)In(Ni@Sn9)]5− with [(Ni@Ge9)Ni(Ni@Ge9)]4−, which has four fewer valence electrons, sheds some light on possible mechanisms that lead to the fusion of cluster fragments.